Auto-generation of passive scalable macromodels for microwave components using scattered sequential sampling. Issue 6 (December 2014) - Sadek, Sawsan; Essaaidi, Mohammed; Chemmangat, Krishnan; Dhaene, Tom; Knockaert, Luc
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents a method for automatic construction of stable and passive scalable macromodels for parameterized frequency responses. The method requires very little prior knowledge to build the scalable macromodels thereby considerably reducing the burden on the designers. The proposed method uses an efficient scattered sequential sampling strategy with as few expensive simulations as possible to generate accurate macromodels for the system using state-of-the-art scalable macromodeling methods. The scalable macromodels can be used as a replacement model for the actual simulator in overall design processes. Pertinent numerical results validate the proposed sequential sampling strategy.